Tingkat Pengetahuan dengan Sikap Remaja terhadap Pendewasaan Usia Perkawinan - Oktarianita Oktarianita; Bintang Agustina Pratiwi; Henni Febriawati; Padila Padila; Andry Sartika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the level of knowledge with adolescent attitudes towards Maturation Age of Marriage (PUP). This research method is a quantitative research with a cross sectional approach. The results showed that there were 63 female adolescents (63%), the most aged 18-19 years 51 (51%), good knowledge 65 people (65%) and a positive attitude of Maturation of Marriage Age (PUP) namely 61 people (61 %). In conclusion, there is no relationship between the level of knowledge with adolescent attitudes towards Maturation Age of Marriage. Keywords: Age of Marriage Maturity, Adolescents, Attitudes, Knowledge Level